A Writer's reference - Hacker, Diana, 1942- 4 0 16; Sommers, Nancy I.;Jehn, Thomas Robert.;Rosenzweig, Jane.; 5 (Boston : Bedford/St. Martin's, 2009)
A reference guide for writers that provides rules and practical advice on composition, revisions, academic writing, sentence style, word choice, grammar, challenges of being multilingual, punctuation, mechanics, and researching; and includes Modern Language Association (MLA) and American Psychological Association (APA)/Chicago Manual of Style (CMS) documentation.
Spiral-bound.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Rhetoric;Grammar;Grammar -- English language;English language;Report writing;English language;Rhetoric;English language;Report writing;English as a second language. -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Textbooks for foreign speakers.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2